Book Reviews (Journal of Finance, 1993)
Book reviewed in this article: Closed‐End Investment Companies: Issues and Answers . By SETH C. ANDERSON and JEFFERY A. BORN. Boston: Kluwer Academic Publishers, 1992. Pp. ix + 139. The Future of American Banking . By JAMES R. BARTH, R. DAN BRUMBAUGH, J r ., and ROBERT E. LITAN. Armonk, N.Y.: M.E. Sharpe, Inc., 1992 (Columbia University Seminar Series). Pp. xxiii + 207. Bankrupt: Restoring the Health and Profitability of Our Banking System . By LOWELL L. BRYAN. New York: Harper Business, 1991. Pp. x + 314. Principles of Finance with Corporate Applications . By DOUGLAS R. EMERY and JOHN D. FINNERTY. St. Paul: West Publishing, 1991. Pp. xxxii + 898. The MIT Dictionary of Modern Economics . Edited by DAVID W. PEARCE. Cambridge, Mass.: The MIT Press, 1992. Pp. xii + 474. Futures and Options: Theory and Applications . By HANS R. STOLL and ROBERT E. WHALEY. Cincinnati: Southwestern Publishing Co., 1993. Pp. xii + 419.